Hemichorea associated with gabapentin therapy with hypoperfusion in contralateral basal ganglion -- a case of a paraplegic patient with neuropathic pain. - Lai M; Wang T; Chang C; Tsai K; Chang S (Journal of Clinical Pharmacy & Therapeutics, 2008)
Functional imaging in patients with movement disorders has suggested abnormalities of regional cerebral blood flow (rCBF). We describe a patient with thoracic cord lesion with subsequent severe neuropathic pain. Right hemichorea developed and was related to adjunctive therapy with gabapentin. The patient's hemichorea decreased gradually after cessation of gabapentin. The study of rCBF revealed hypoperfusion in the contralateral basal ganglia compared with the previous study of rCBF. Our patient is the first patient with neuropathic pain, treated with gabapentin who developed hemichorea, in the absence of brain lesions. Imaging studies of rCBF showed a perfusion defect in the contralateral basal ganglion.